PELATIHAN RESIN MEJA KAYU UNTUK PENINGKATAN PERAN SERTA MASYARAKAT DALAM PENGEMBANGAN KEMITRAAN PARIWISATA DI KABUPATEN KAMPAR - Amrizal Muchtar; Hanafi Hanafi (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Kampar Regency is an area that has the availability of natural wood products of 6,595,705 m and there is also a lot of this wood that is not used because of defects, but basically it can be creatively processed into handicraft and furniture products. The existence of this abundant wood became an inspiration for the Tourism and Culture Office of Kampar Regency, through the program in the Sub-Activity of Increasing Community Participation in Tourism Partnership Development for the 2021 Fiscal Year, which raised an activity with the theme